21. Association of MRSA Prevalence and Hospital-level Antibiotic Use: A Retrospective Study Across 122 Acute-care Hospitals. (31st December 2020) - Livorsi, Daniel J; Nair, Rajeshwari; Lund, Brian; Alexander, Bruce; Beck, Brice; Goto, Michihiko; Perencevich, Eli N
Abstract: Background: The prevalence of methicillin-resistant Staphylococcus aureus (MRSA), varies across geographic regions, which could contribute to regional variation in antibiotic use. In this study, we evaluated whether local MRSA prevalence rates were associated with hospital-level antibiotic use across the Veterans Health Administration (VHA). Methods: This retrospective cohort included all acute-care patients admitted in VHA hospitals during 2016. Anti-MRSA antibiotics were identified per National Healthcare Safety Network definitions and use was quantified as days-of-therapy (DOT) per 1000 days-present. Hospital-level MRSA prevalence (colonization and/or infection) was determined by calculating the proportion of admissions with a positive MRSA nasal swab and/or a MRSA-positive clinical culture obtained ≤1 day before or ≤2 days after admission. Negative binomial regression models were used to determine the association between a hospital's MRSA prevalence and its antibiotic use, after accounting for intra-hospital clustering, patient case-mix, month of admission, and use of hospital-based stewardship strategies. Results: There were 548, 476 admissions across 122 hospitals. The median rate of MRSA prevalence at admission was 8.0% (IQR 6.7–9.7%). Hospital level median use of anti-MRSA and total antibiotics was 96.5 (interquartile range [IQR] 81.1–116.9) and 562.1 (IQR 505.9–631.6) DOT per 1, 000 days-present, respectively. In a hospital-level risk adjusted analysis, a hospital's MRSA prevalance was significantly associated with its monthly use of both anti-MRSA and total antibiotics (IRR=1.05, 95% 1.02–1.07; IRR=1.02, 95% CI, 1.01–1.03). A 5% increase in the hospital's MRSA prevalence was associated with an increase in the monthly use of anti-MRSA antibiotics and total antibiotics by 23.6 and 8.3 DOT per 1, 000 days-present, respectively. Conclusion: Higher hospital-level MRSA prevalence was associated with significantly higher rates of antibiotic utilization, even after adjusting for case-mix and reported antibiotic stewardship strategies. Future benchmarking of anti-MRSA antibiotic use across hospitals may need to risk-adjust using baseline rates of MRSA prevalence. Disclosures: Daniel J. Livorsi, MD, MSc, Merck and Company, Inc (Research Grant or Support) Rajeshwari Nair, PhD, Merck and Company, Inc. (Research Grant or Support)